Ozone therapy in periodontics: A meta-analysis - R Deepthi; Shivaprasad Bilichodmath (Wolters Kluwer Medknow Publications, 2020)
Gingival and periodontal diseases constitute a major distress in the field of dentistry. The greater part of the contributing and etiologic factors are diminished or treated with all forms of ozone. Ozone which is well known for its antimicrobial and tissue regenerative properties is indicated in all the stages of gingival and periodontal diseases. The aim of this study was to review literature on the effects of ozone as an adjunct to mechanical therapy in periodontitis patients. A search of literature was conducted to identify articles of ozone therapy in periodontitis published during the period from January 1, 2010, to July 30, 2018. PubMed, Medline, Embase, Cochrane, and Google Scholar search and hand searching of journals were conducted to identify relevant articles. The search strategy employed both dental subject headings and free-text terms. Out of a total of 123 studies that fit the initial inclusion criteria, 117 studies were further excluded. Only six studies were included in the meta-analyses. A high level of heterogeneity in the selected studies was found as demonstrated by Q-value of 10.241 and I2 value of 80.49%. However, the funnel plots showed symmetrical shape, with prevalence studies indicating absence of publication bias. Ozone therapy can be used effectively as an adjunct to scaling and root planing in the treatment of periodontitis.